Prescription of training load in relation to loading and unloading phases of training (Rowing Australia, 2015)
Performance enhancement and athlete wellbeing is the collective responsibility of the coachand all support staff (including but not limited to Physiology, Medicine, Strength and Conditioning, Physiotherapy, Nutrition, Psychology). Although driven by the coach and athlete, performance enhancement and athlete wellbeing should not be `owned` by any single entity or discipline. Systematic training prepares the athlete for the demands of the sport such that both performance and safety are enhanced. It is acknowledged that moderate to high training loads improve performance and are protective against injury. The skill in planning high performance training programs is in balancing the risks and benefits associated with ensuring an adequate training stimulus without accumulating excessive training stress. Recent evidence has highlighted a link between match availability rates of players and performance in team sports. A similar relationship between injury burden and performance in individual sports has been observed from analysis of internal data with athletes reporting injuries in the month prior to World Championships at risk of sustaining an in-championship injury. Importantly, if substantial amounts of training are modified,individual athletes aresignificantly less likely to achieve their goals. This paper will focus on the process to attain required training levels and specifically, appropriate load strategies following training troughs due to planned rest, tapering or injury/illness. Planning training load is imperative to maximise exposure to training to allow adaptation and skills developmentto occur thus improving the opportunity to perform.If an athlete trains at 60% of their normal volume and intensity for 2 weeks, it takes 10 days to progressively return to full training load to reduce injury risk. Longer breaks in training and greater drops in volume and intensity require a longer progressive return to full training to reduce injury risk.